Phenological Parameters of Leeks Grown as a Main Crop at Different Planting Dates - kizi, Makhmudova Muazzam Sobir; Iskandarovna, Khamdamova Elnura (American Journal of Biodiversity, 2025)
The demand for leek cuttings in the food industry is growing daily, and therefore the need for a fast and high-quality supply of this product to farmers is also increasing. To meet this demand, this article describes the correct determination of planting time and phenological parameters when growing leeks as a main crop from seedlings at different planting times.